Amide Bond Activation - Szostak, Michal (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The amide bond represents a privileged motif in chemistry. The recent years have witnessed an explosion of interest in the development of new chemical transformations of amides. These developments cover an impressive range of catalytic N-C bond activation in electrophilic, Lewis acid, radical, and nucleophilic reaction pathways, among other transformations. Equally relevant are structural and theoretical studies that provide the basis for chemoselective manipulation of amidic resonance. This monograph on amide bonds offers a broad survey of recent advances in activation of amides and addresses various approaches in the field.